A rare case of Aspergillosis in a goat (Indian Journal of Veterinary Pathology, 2025)
A goat of 2 years was presented for necropsy examination. Postmortem examination of the animal revealed lungs with multiple firm creamish nodules which were observed in both the lungs. Histopathological examination of lungs revealed a typical pyogranulomatous reaction with fungal hyphae in a central necrotic area. The hyphae were demonstrated by Grocott’s and PAS staining. Cultural examination revealed bluish-green colonies on Sabouraud dextrose agar, indicating Aspergillosis. Lactophenol cotton blue staining revealed conical heads with a uniseriate row of phialides on the upper two-thirds of the vesicle.